Microbial characterization of cow pat pit and biodynamic preparations used in biodynamic agriculture - RAM, R A; SINGHA, ATUL; KUMAR, A (The Indian Journal of Agricultural Sciences, 2019)
As of today, biodynamic agriculture is practised across 60 countries of the world. Cow pat pit (CPP) and biodynamic preparations (BD) are the key components of biodynamic agriculture. However, there a is dearth of scientific explanation on account of their mode of action. CPP and BD preparations are very effective in compost production, soil health management and eventually, enhancing the yield and quality of crop produce. Efficacies of these preparations were evaluated with isolation and characterization of beneficial microbes. Study revealed that CPP contained maximum gram positive and gram negative bacteria (184 ± 14 × 105cfu/g), (225 ± 9 × 105cfu/g) and Rhizobium (310 ± 24 × 107cfu/g), while BD-507 contained the highest number of actinomycetes (792 ± 194 × 106cfu/g) and Azotobacter (201 ± 14 × 105cfu/g) among the all preparations. Actinomycetes isolated from CPP and BD-507, showed ammonia, indole acetic acid (IAA), siderophore and HCN producing activities. Out of total isolated microbes from CPP and BD preparations, 9 isolates showed high ammonia, 23 IAA, 18 siderophore and 12 HCN producing activities. Based on the study, it may be suggested that CPP and BD preparations may be used as bio-inoculants and combined with compost in organic production of various crops.